The State’s Disinformation Campaigns and the Young Iranian Dissidents’ Participatory Media Literacy - Azeri Matin (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
State media plays a central role in empowering the authoritarian regimes to subjugate their people. In Iran, this undemocratic practice largely takes place in the form of information manipulation where the state-run national media generate deceptive messages to sway the masses and influence the public opinion. Yet, the rapid advancements of communication technologies in the past two decades have gradually shaken this power structure in a variety of ways, among them enabling a form of participatory media literacy (PML) among dissident youth. Characterized by virtual social networking, PML has progressively grown from the youth’s online activism and political engagement, especially during the periods of social unrest. Intersecting ‘participatory culture’, this form of media literacy emanates from a rather organic and spontaneous progression in knowledge and experience acquisition which distinguishes it from the conventional learning of the subject in the educational institutes, both in terms of the scope limitation as well as the learners’ deliberation. Typically, the process involves the members’ active participation (content sharing, discussions and critical evaluation of the presumably disinformation cases) in social media and other oppositional online communities. Taking Telegram as a popular social networking platform for the young activists’ PML, this study uses netnography to examine the contents of some of the subversive Telegram channels (STCs), providing examples of the disinformation cases discussed/evaluated by the members. Ultimately, it is argued that in authoritarian nations, PML offers opportunities for nullifying the state’s disinformation campaigns and their preventive effects on the progress of social movements and political change.